SOME OPERATIONS ON INTERVAL VALUED INTUITIONISTIC ANTI FUZZY PRIMARY IDEALS OVER.... - PALANIVELRAJAN, M.; INBAM, C.; ADILAKSHMI, E. (International Journal of Mathematical Archive, 2018)
In this paper, we introduce the interval valued intuitionistic anti fuzzy primary ideal (IVIAFPI) and its basic operations. Also we establish some of their properties.